Social stakeholders' pressure on environmental accounting reporting in small and medium enterprises – evidence from China - Sulaiman Tahajuddin; Zhao Xin; Abdul Wahid Mohd. Kassim; Raman Noordin (International Journal of Research in Engineering, Science and Management, 2021)
This study aims to examine the effect of pressure from social stakeholders on environmental accounting reporting (EAR) in small and medium enterprises (SMEs) in Shan Xi Province, China. Using an online survey, this study sampled from 90 respondents in SMEs. The data was then analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 3.3.2. The empirical evidence shows that there is a positive and significant influence of the social stakeholders' pressure on EAR, especially, the pressure from media and community. The findings of this study suggest that community and media do improve the environmental accounting reporting in SMEs in Shan Xi Province, so that can improve SME's performances concerning the environment, inventory and controlling costs, efficient technologies with less pollution, non-polluting products.